Narrating Muhammad’s Night Journey: Tracing the Development of the Ibn Abbas Ascension Discourse by Frederick S. Colby (Albany: State University of New York Press, 2008. 314 pages.) (American Journal of Islam and Society, 2009)
The story of Muhammad’s night journey to Jerusalem and ascent to heavenenjoys huge popularity across the Muslim world. It has functioned as a vehiclefor many forms of artistic expression throughout the ages as well as havingbeen subject to much literary development. In addition, it has impactedand interacted with legal and theological dogma that may be seen in elementsranging fromthe establishment of the five daily prayers (on which seethe fascinating essay by Ron Buckley, “The Isra’/Mi`raj and the prescriptionof the five daily prayers,” in Andreas Christmann, Robert Gleave [eds.],Studies in Islamic Law: A Festschrift for Colin Imber [Oxford: Oxford UniversityPress, 2007], 23-49) to the conceptualization of paradise and hell (see the treatment in Nerina Rustomji, The Garden and the Fire: Heaven andHell in Islamic Culture [NewYork: Columbia University Press, 2008], especiallypp. 26-39).Historically, the narrative makes its basic appearance in some of the earliestMuslim texts, for example, in Ibn Ishaq’s eighth-century work entitledLife ofMuhammad. The emergence of the story has been seen (in, for example,Brooke Olson Vuckovic, Heavenly Journeys, Earthly Concerns: TheLegacy of the Mi`raj in the Formation of Islam [New York and London:Routledge, 2005]) as an important element in the historical formation ofIslamic identity; it has also been seen by some as having had a powerfulimpact on European imaginings of the hereafter, as found in medieval writerssuch as Dante ...